Efektivitas Penyimpanan Google Drive dalam Menyimpan Data - Nursakiah, Nursakiah; Andi Quraisy; Ilhamsyah; Ummu Kalsum (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
This training aimed to improve the skills of MI DDI Lampa teachers in utilizing Google Drive as an effective data storage medium to support administration and learning. The activities were carried out through interactive lectures, demonstrations, and hands-on practice. These included creating folder structures, uploading and managing files, document search, sharing files with permission settings, collaborating on Google documents, and strengthening account security. Fourteen teachers participated. Evaluation was conducted using a pretest–posttest, checklist-based practical observations, and a satisfaction questionnaire. Results showed an increase in knowledge, with scores shifting from predominantly low in the pretest to predominantly high in the posttest. Practical observations demonstrated excellent mastery of core skills, particularly file uploading and folder organization, while advanced features such as version history, search and filtering, and setting secure sharing links still needed reinforcement. Overall, Google Drive was deemed effective because it facilitated cross-device access, accelerated collaboration, and streamlined the school's digital archiving. Follow-up measures were recommended, including school archiving standards, strengthened sharing security, and practical guidance for more consistent and secure use